Changing perspectives of corporate governance in India. (1st January 2013) - Kavitha, D.; Nandagopal, R.
The nature of corporate governance in India is constantly changing due to the interactions of Indian firms with global markets. The existing corporate governance regime in India has borrowed largely from the UK and US systems. The compatibility of these models to the Indian situation is being questioned in recent days. The Indian corporate governance reform process and the recommendations of various committees have been examined in detail to substantiate the basic argument. This paper argues that convergence towards the Anglo-American model of corporate governance may not suit the Indian circumstances. The study indicates that the corporate governance model followed in a country should be specific to its micro and macro environment. A unique model that considers the social, political, economic and legal systems of India would be the most appropriate one. But the practicability of such a concept would require ample time and motivation.